'What's new for you?': Interlocutor-specific perspective-taking and language interpretation in autistic and neuro-typical children. (February 2020) - Abbot-Smith, Kirsten; Williams, David; Matthews, Danielle
Highlights: We developed a condition in which participants had to consider that a speaker would be excited about an object that was new for her. Autistic children did not differ from neuro-typical peers when using interlocutor-generic perspective to interpret referring expressions. Autistic children performed more poorly than controls when using interlocutor-specific perspective to interpret referring expressions. Abstract: Background: Studies have found that children with Autism Spectrum Disorder (ASD) are more likely to make errors in appropriately producing referring expressions ('the dog' vs. 'the black dog') than are controls but comprehend them with equal facility. We tested whether this anomaly arises because comprehension studies have focused on manipulating perspective-taking at a 'generic speaker' level. Method: We compared 24 autistic eight- to eleven-year-old with 24 well-matched neuro-typical controls. Children interpreted requests (e.g. 'Can I have that ball?') in contexts which would be ambiguous (i.e. because the child can see two balls) if perspective-taking were not utilized. In the interlocutor-specific perspective-taking condition, the target was the particular object which was new for the speaker. Children needed to take into account what the speaker had played with before and the fact that they were now expressing excitement about something new. In two control 'speaker-generic' conditions we tested children's ability to take the visual perspective of the speaker (where any speaker who stood behind a particular barrier would have the same perspective). Results: The autistic group were significantly less likely to select the target and significantly more likely to request clarification in the 'interlocutor-specific' condition. Performance in the 'interlocutor-generic' (visual) perspective taking conditions did not differ between groups. Conclusion: Autistic children, even those who are not intellectually-impaired, tend to have more difficulty than neuro-typical peers in comprehending referring expressions when this requires understanding that people comment on what is new for them.